PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN CUSTOMER VALUE TERHADAP KEPUASAN PELANGGAN PADA HOTEL NEW RESTY MENARA PEKANBARU - Harmiko "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence customer relationship management (CRM) and customer value have on customer satisfaction at the New Resty Hotel Menara Pekanbaru. The sample in this study was taken as many as 100 respondents and the technique used was excidental sampling. The data in this study used the survey method through a questionnaire filled out by customers. Data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS18 program.This research was conducted at the New Resty Hotel Menara Pekanbaru, located on Sisingamaraja No.89 Pekanbaru. From the method of collecting data using a questionnaire, hypothesis testing uses multiple linear analysis methods. It is known that the results of the study show that Customer Relationship Management (CRM) has a positive effect on customer satisfaction, Customer Value has a positive effect on customer satisfaction, and a significant effect between Customer Relationship Management (CRM) and Customer Value on Customer Satisfaction at the New Resty Hotel Menara Pekanbaru. Creating a relationship so that it can provide positive value to customers and increase the ability to serve customers in order to realize professional servicesKeywords: Customer Relationship Management (CRM), Customer Value, and Customer Satisfacti.